Intertextuality in Tafsīr al-Jāmi‘ li Ahkām al-Qur’ān by al-Qurṭubī - Jullul Wara; Ahmadi Ahmadi; Lukman Marsaton (Yayasan Pesantren Mahasiswa An-Nur, 2024)
This study critically examines the intertextual patterns in Tafsīr al-Jāmi‘ li Aḥkām al-Qur’ān by al-Qurṭubī, focusing on its relationship with earlier works, particularly Aḥkām al-Qur’ān by Ibn al-‘Arabī. Intertextuality in this context refers to external influences and connections between texts, exploring how al-Qurṭubī engaged with, borrowed from, and elaborated on previous tafsīr literature. The research employs a descriptive-analytical method grounded in Julia Kristeva’s intertextual theory and is conducted through library research. The findings reveal distinct intertextual patterns, with the most prominent expansion pattern. This pattern involves quoting source texts and enriching them through elaboration and additional reasoning, demonstrating al-Qurṭubī’s intellectual engagement and methodological rigor. These results highlight the dynamic interplay between tradition and originality in al-Qurṭubī’s work, offering new insights into the intertextual practices in classical Islamic scholarship.